On the design and aerodynamic performance of joined-wing aircrafts - Teo, Alvin Zhen Wei (2018)
The increase in air traffic in the last decade has given further incentive to explore unconventional configurations which may have added aerodynamic efficiency. The configuration of choice in the study is the joined-wing configuration. An experimental and numerical study was carried out to investigate the aerodynamic characteristics, as well as the flow behaviour, of two joined-wing configurations, one with negative stagger and one with positive stagger, as well as a typical commercial aircraft configuration for reference, at various orientations by permuting a combination of angles of attack, sideslip angle as well as roll angle. Force balance measurements and surface oil flow visualization were carried out in closed-loop subsonic wind tunnel to examine the lift/drag behaviour as well as the longitudinal, directional and lateral stability. Through the wind tunnel experiments, it was found that both joined-wing configurations do not show sharp dips in the lift coefficient throughout the range of angles of attack, unlike the reference aircraft at approximately 15°. However, in general, it was found that the lift coefficients of the joined-wing aircraft were lower than that of the reference across the range of angles tested, and do not show any conclusive evidence of increased aerodynamic efficiency over the reference configuration at the tested Reynolds numbers. In addition, there were some minor problems in terms of the lateral stability for the positively staggered joined-wing configuration. Numerical simulations were carried out at similar conditions with a commercially available code for corroboration and to provide additional data not collected in the wind tunnel experiments for further analysis. The trends in the numerical simulations matched the wind tunnel experiments quite well, especially for the positively staggered joined-wing configuration. The streamlines generated from the numerical simulation results also greatly aided in the analysis and interpretation of the surface oil flow visualization results. However, the numerical simulations were also unable to accurately model the flow physics of the laminar separation bubble at the lower AOAs. In addition, the discrepancies with the experimental results were higher when combinations of roll and yaw were implemented. In the course of designing the wind tunnel test model, difficulties were faced when attempting to fabricate with conventional machining methods. Hence, modern additive manufacturing techniques were used. However, due to the method of fabricating the wings and the material used, wing deflections were also observed. These deflections were photographed and digitized, then reproduced as a smooth curve through regression. It was found that the deflection magnitudes are tightly associated with the lift curve behaviour.